2019
DOI: 10.1016/j.devcel.2018.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Signaling Promotes Longevity by Adjusting Mitochondrial Activity

Abstract: Highlights d Lysosomal lipid messenger signaling actively regulates mitochondrial ß-oxidation d Mitochondrial ß-oxidation modulates electron transport chain complex II activity d Lysosomal and mitochondrial pro-longevity signaling converge on JUN-1 d Organelle coordination improves metabolic balance, redox homeostasis, and longevity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 67 publications
1
75
0
Order By: Relevance
“…to induce and regulate a complex signaling network between mitochondria, the nucleus (Quiros et al, 2016), other organelles, such as lysosomes (Ramachandran et al, 2019), and the cytosol (D'Amico et al, 2017), resulting in increased cell stress resistance that can improve health and extend lifespan. Of particular interest is the recent observation that early developmental transient redox stress in Caenorhabditis elegans could indeed modify the methylation state of the genome, and lead to increased stress resistance, improved redox homeostasis, and prolonged lifespan (Bazopoulou et al, 2019).…”
Section: Ros and Mitochondria In Aging Progressionmentioning
confidence: 99%
“…to induce and regulate a complex signaling network between mitochondria, the nucleus (Quiros et al, 2016), other organelles, such as lysosomes (Ramachandran et al, 2019), and the cytosol (D'Amico et al, 2017), resulting in increased cell stress resistance that can improve health and extend lifespan. Of particular interest is the recent observation that early developmental transient redox stress in Caenorhabditis elegans could indeed modify the methylation state of the genome, and lead to increased stress resistance, improved redox homeostasis, and prolonged lifespan (Bazopoulou et al, 2019).…”
Section: Ros and Mitochondria In Aging Progressionmentioning
confidence: 99%
“…Additionally, the lipase LIPL-4 promotes longevity in Caenorhabditis elegans by harnessing its degradative activity within the lysosome to establish a lipid–protein chaperone complex that translocates to the nucleus and promotes the transcriptional activity of NHR-49 and NHR-80 nuclear hormone receptors ( Folick et al, 2015 ). Nuclear hormone receptors regulate the expression of genes related to mitochondrial metabolism and the oxidative stress response, a mechanism linked to organismal longevity due to downstream activation of mitochondrial ß-oxidation and ETC activity ( Folick et al, 2015 ; Ramachandran et al, 2019 ). Biochemical and high throughput metabolomic analyses revealed that the nuclear complex generated by LIPL-4 in C. elegans is comprised of the lipid species oleoylethanolamide (OEA) and the lipid chaperone LBP-8.…”
Section: Metabolic Organelle Network Regulate Stem Cell Fatementioning
confidence: 99%
“…Biochemical and high throughput metabolomic analyses revealed that the nuclear complex generated by LIPL-4 in C. elegans is comprised of the lipid species oleoylethanolamide (OEA) and the lipid chaperone LBP-8. All three elements of this signaling pathway are structurally or functionally conserved in mammals (LIPL-4 and NHR-80 are homologous to mammalian LIPA and HNF4, respectively; the mammalian lipid metabolism transcription factor PPARα is activated by OEA) ( Fu et al, 2003 ; Folick et al, 2015 ; Ramachandran et al, 2019 ), thus similar lysosome-nuclear signaling mechanisms are likely to impact cell fate determinant transcriptional programs in mammalian systems.…”
Section: Metabolic Organelle Network Regulate Stem Cell Fatementioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence suggests that longevity is associated with a specific lipid profile characterized by an increased ratio of monounsaturated fatty acids (MUFAs) to polyunsaturated fatty acids (PUFAs), both in humans and in C. elegans (Schroeder and Brunet, 2015). However, even though these results might suggest that elevated levels of PUFAs may accelerate aging on their own, recent studies suggest that the increased abundance of specific PUFAs (arachidonic acid [AA] and dihomo-g-linolenic acid [DGLA]) or other bioactive lipids (oleoylethanolamide [OEA]) may independently, or through their role in a lipid signaling cascade, extend lifespan through their effects on autophagy, gene expression, and/or mitochondrial activity (Folick et al, 2015;O'Rourke et al, 2013;Ramachandran et al, 2019).…”
Section: Introductionmentioning
confidence: 99%